The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1128/aem.49.3.509-516.1985
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal cometabolism of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) and its breakdown products

Abstract: Resting cells of bacteria grown in the presence of diphenylmethane oxidized substituted analogs such as 4-hydroxydiphenylmethane, bis(4-hydroxyphenyl)methane, bis(4-chlorophenyl)methane (DDM), benzhydrol, and 4,4'-dichlorobenzhydrol. Resting cells of bacteria grown with benzhydrol as the sole carbon source oxidized substituted benzhydrols such as 4-chlorobenzhydrol, 4,4'-dichlorobenzhydrol, and other metabolites of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT), such as DDM and bis(4-chlorophenyl)acetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 19 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…The fact that DDD did not accumulate stoichiometrically with DDT loss in the surfactantamended microcosms ( Figure 5) suggests that some DDD degradation occurred. Although most earlier work indicated that DDD is the primary anaerobic metabolite of DDT (Pfaender and Alexander, 1972;Subba-Rao and Alexander, 1985;and Wedemeyer, 1966), it does not always accumulate stoichiometrically with DDT loss (You et al, 1996), and metabolites downstream of DDD have been observed (Pfaender and Alexander, 1972).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The fact that DDD did not accumulate stoichiometrically with DDT loss in the surfactantamended microcosms ( Figure 5) suggests that some DDD degradation occurred. Although most earlier work indicated that DDD is the primary anaerobic metabolite of DDT (Pfaender and Alexander, 1972;Subba-Rao and Alexander, 1985;and Wedemeyer, 1966), it does not always accumulate stoichiometrically with DDT loss (You et al, 1996), and metabolites downstream of DDD have been observed (Pfaender and Alexander, 1972).…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that for other soils, solutes, surfactants, and concentration ranges, linear solubilization behavior will not necessarily be observed. Equilibrium models to describe the solubilization of hydrophobic solutes under a broader range of conditions are available in the literature (Edwards et al, 1991(Edwards et al, , 1994a(Edwards et al, , and 1994bJafvert et al, 1995;Sun et al, 1995;and Yeom et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of HCl from the parent compound DDT occurs via reductive dechlorination and is catalyzed by both biotic and abiotic systems [3]. Bacteria and fungi from many di¡erent genera are capable of a¡ecting this transformation [2,4]. While some organisms have been reported to further degrade DDD in liquid culture by continued reductive dehalogenation [4^6] or by hydroxylation [2] of the aliphatic moi-ety, there is limited information on the direct aerobic transformation of DDD via oxidative attack of the aromatic ring [7].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, as with the biodegradation of DDT, the biodegradative abilities of fungi have been virtually ignored. 27 This example is striking, for DDT is perhaps the most widely studied xenobiotic with regard to its resistance to microbial biodegradation and concomitant environmental persistence.…”
Section: Environmental Considerationsmentioning
confidence: 99%
“…During the 1950s and 60s scientists and the public became aware of the real and potential problems associated with the introduction of persistent chemicals, especially organohalides, into the environment. Since that time there have been numerous reports documenting the ability of a wide variety of bacteria and fungi to degrade even the most recalcitrant molecules in the laboratory and in the environment.28 Even DDTl, 27 and highly chlorinated PCB mixtures21 28g 2B are susceptible to biodegradation, sometimes at surprisingly high rates.…”
Section: Environmental Perspectivesmentioning
confidence: 99%